Study On Phytochemical and Antioxidant Properties of Padina gymnospora and Ulva lactuca: Life Sciences-Marine Biology - Praba, N.; Sumaya, Dr. S. (International Journal of Life Science and Pharma Research, 2022)
Seaweed constitutes one of the commercially important living renewable resources in the marine ecosystem.Seaweeds have antimicrobial, antioxidant, and anti-inflammatory properties. The aim of the study is to estimate the phytochemicals and antioxidant activity of Padina gymnospora and Ulva lactuca. The antioxidant properties and phytochemical analysis of Padina gymnospora and Ulva lactuca collected from the Gulf of Mannar during the low tide period were analyzed.The study's objective is to analyze the phytochemical and antioxidant activities using methanol as solvent. Antioxidant activities were determined using 2,2-diphenyl-1-picryl-hydrazyl (DPPH) assay treated with methanol and Phytochemical analysis carried out by Folin-Ciocalteu reagent. Antioxidants and phytochemicals in seaweeds provide healthpromoting effects and protect against non-communicable diseases such as Cancer, arthritis, diabetes, obesity, etc. The results reveal that antioxidant activities were higher in Padina gymnospora in methanol solvent than in Ulva lactuca. The percentage of inhibition of Padina gymnospora and Ulva lactuca was 61.5 and 64.5 respectively. IC50 value of Padina gymnospora and Ulva lactuca was 60.4 and 60.6 respectively.The preliminary phytochemical analysis of Padina gymnospora and Ulva lactuca was found to contain Alkaloids, Steroids, Terpenoids, Glycosides. To know the efficiency of green seaweed Ulva lactuca with brown seaweed Padina gymnospora the study was carried out. The highest flavonoid content was recorded in brown seaweed Padina gymnospora (25.5±0.02mg REg-1) compared toUlva lactuca (19.32±0.5mg REg-1). The total phenolic content was highest in Padina gymnospora (3.7±0.06mg GAEg-1) whereas Ulva lactuca contained (2.81±0.3mg GAEg-1). Therefore, the present work recommends consuming seaweeds in our regular diets to have a healthy lifestyle. From the current study of phytochemical and antioxidant rich seaweeds can be incorporated in the formulation of drugs used for treating various non- communicable diseases prevailing in the present era. Keywords: , , ,